Ultrasound Assessment of Gastric Volume After Bariatric Surgery: A Case Report. Issue 1 (1st January 2019) - Pai, Sher-Lu; Bojaxhi, Elird; Logvinov, Ilana I.; Porter, Steven B.; Feinglass, Neil G.; Robards, Christopher B.; Torp, Klaus D.
Abstract : Gastric ultrasound is emerging as a tool that can be used to assess gastric content and volume in patients with an unknown fasting history. This information can impact the choice of anesthetic technique or the timing of surgery due to the presumed risk of aspiration. Currently, no data are available regarding the use of gastric ultrasound for patients who have had prior gastric operations, despite the increasing number of patients undergoing bariatric surgery. Our experience suggests that a patient with a prior Roux-en-Y gastric bypass may present with altered anatomy, rendering gastric ultrasound an ineffective technique to assess the volume of ingested food or liquid.